A topotactic transition in a liquid crystal compound. Issue 46 (5th June 2015) - Centore, Roberto; Capitolino, Valeria; Cerciello, Francesca; Tuzi, Angela; Borbone, Fabio; Carella, Antonio; Roviello, Antonio
Abstract : The title compound has two crystal phases related by an enantiotropic single-crystal-to-single-crystal transition and a nematic liquid crystalline phase before transition to the isotropic liquid phase. Abstract : The title compound, bis(4-butyloxyacetophenon)azine, exhibits a rich phase behavior. It has two different crystal phases and one liquid crystal phase before transition to the isotropic liquid phase. The liquid crystalline phase is nematic. All the phase transitions of the compound are reversible. In particular, the solid–solid transition at 83 °C is single-crystal-to-single-crystal as proven by optical and electron microscopy and X-ray diffraction analysis and it shows a remarkable degree of reversibility; single crystals can undergo several cycles of transition between the two phases without any damage. The crystal phase stable at lower temperature has been fully characterized by single crystal X-ray analysis. It shows an arrangement of the molecules in layers in the plane ( a, b ), with the layers piled up along c without interdigitation of the alkyl tails of molecules belonging to consecutive layers. The crystal phase stable at higher temperature is disordered.